Petrography and illite crystallinity of the Lesser Himalayan metasediments, Gorkha Narayangarh section, central Nepal - Paudyal, Kabi Raj; Pokharel, Tara Prasad; Paudel, Lalu Prasad (Bulletin of the Department of Geology, 2011)
Geological study was carried out in the Lesser Himalaya from Gorkha-Narayangarh section of central Nepal aiming to assessthe metamorphism of the area. The area consists of the Kunchha Formation, Fagfog Quartzite, Dandagaon Phyllites, NourpulFormation, Dhading Dolomite, Benighat Slate and the Robang Formation of the Nawakot Complex. Systematic study onpetrography and illite crystallinity was performed in the samples representing all types of lithology and formations. Bothpetrography and illite crystallinity show that the rocks south of Anbu Khaireni belong to chlorite zone. Biotite and garnet zonesare observed only in the north of Anbu Khaireni. The metamorphic zones are inverted as in the other parts of the Lesser Himalaya. DOI: http://dx.doi.org/10.3126/bdg.v14i0.5441 Bulletin of the Department of Geology Vol.14 2011, pp.67-76